Political Informality on Social Media: The Impact of Influencer Involvement in the Central Sulawesi Gubernatorial Election Contest on the Institutionalization of Democracy - Fitriningsih; Sunardi; Sitti Rabiatul Wahdaniyah Herman (Journal of Governance and Social Policy, 2026)
This research will examine the relationship between the state and citizens mediated by social media. It examines two social contexts: first, the digital revolution, which has driven the trend of increasing social media use, and second, the high level of interaction on social media, which has created space for the presence of informal third parties. These third parties take the form of "influencers." Facilitated by social media, influencers play the role of intermediaries between the state and citizens. They act as a bridge, often creating an ambivalent relationship between the state and citizens. On the one hand, the presence of influencers has a negative impact on the institutionalization of democracy, while on the other, it has a positive impact. Focusing on the context of the 2024 gubernatorial election in Central Sulawesi, this research will examine the impact of influencer ambivalence on the institutionalization of democracy.